(untitled) (Global Journal of Science Frontier Research, 2015)
In this article we review the types of natural and synthetic materials that are being used in brain tissue engineering applications for traumatic brain injury and stroke. We analyse modifications of scaffolds including immobilizing drugs, growth factors and extracellular matrix molecules to improve central nervous system regeneration and functional recovery. This review attempts to outline the varieties of biomaterial parameters that are applied as biophysical and biochemical signals to direct NSC fate and behaviour. The understanding on the interaction of NSCs decision and biomaterial parameters is helping to advance NSCs-based clinical approaches for nerve tissue regeneration and repair.